Accounting and the shifting spheres: The economic, the public, the planet - Vollmer, Hendrik (Accounting, Organizations and Society, 2024)
Accounting's sense of place and purpose is informed by social imaginaries. The imaginaries of the sphere of the economic, the public, and the planet help accountants make sense of their surroundings and the world at large, help them coordinate and form alliances with other forms of expertise, and frame their understanding of what matters. Recent disputes over materiality and declarations by the profession to serve the “people and the planet” suggest that accounting's sense of place and position is variable, yet its long-standing imaginaries indicate that it is also regular and steady. By discussing how imaginaries of the economic, the public and the planet prefigure how accounting connects us with the world from our “bubbles” (Sloterdijk), the paper makes a case for paying more attention to how these imaginaries shape our understanding of what accounting is about and can become, how they might lock accounting into position, and us with it.